Organisation and analysis of genomic counsellors' assessments at the Institute of Oncology Ljubljana in 2023 - Romana Krivec Matijašič; Tina Kerševan; Mateja Krajc (Onkologija)
Introduction: In 2021, the role of genomic counsellor was introduced as a new profile in the Slovenian healthcare system, and likewise at the Institute of Oncology Ljubljana (IOL). In the triage process, clinical genetics specialists determine the number of genetic consultations performed by genomic counsellors, who usually provide counselling for patients who require genetic testing for treatment planning. Methods: We evaluated the data on referrals to genetic counselling and the genetic testing of patients referred to genomic counsellors in 2023. The data were obtained from the database of the Department of Clinical Cancer Genetics at OIL. Descriptive statistical methods and bivariate methods were used for analysing the correlation between variables. Results: In 2023, 2,200 pre-testing genetic counselling consultations were performed. Four genomic counsellors performed 30.4% (669/2.200) of all pre-test genetic counselling consultations. 662 out of 669 patients (i.e. 118 men and 551 women) opted for genetic testing. There were 323 (48%) urgent – fast–track listed patients. The test results of the fast–track listed group were received in 29 (±13) days after the first consultation. In 14.5% (96) of the patients tested a pathogenic/likely pathogenic variant (P/LPV) was identified. The most P/LPVs were found in BRCA1/2 genes (57.3%), followed by the ATM gene (14.6%) and CHEK2 gene (10.4%). Conclusion: Introducing a new profile, a registered nurse with special knowledge in genomic counselling, working as a genomic counsellor, is a successful method of ensuring timely patient care. The additional consultations have helped shorten the waiting times for genetic counselling performed by clinical genetics specialists and speed up the process of genetic treatment for patients.